Clinical Manifestations, Treatment and Outcomes of Snake bite cases in a Tertiary care hospital- A Record based Retrospective Study (Journal of Forensic Medicine & Toxicology, 2026)
Introduction: Snake bite is an important occupational hazard in India. Systematic documentation of site of bite, time of  bite, treatment used, duration of hospital stay and outcome will help in contributing towards optimization and efficient  utilization of resources, training of emergency staff handling of snake bites, planning resource allocation, procurement  of medicines. The objectives of the study were to determine the proportion of snake bites with clinical features of envenomation, to  document the clinical signs of envenomation and the medications used in snake bite with regard to dose and duration  and outcomes including duration of stay, complications, need for additional interventions and death. Methods: Data was extracted by a retrospective observational study of case records from the department of General  Medicine in our college, from January 2011 to November 2020 after obtaining approval from ethics committee. Results: In this study, data was extracted from 28 snake bite case records, in which two cases were non-poisonous snake  bites, four cases did not have any signs of envenomation and 22 snake bite cases presented with signs of envenomation of  which 14 snake bite cases received Anti Snake Venom (ASV) in an average dose of 8.35 vials per person as mentioned in  the case records. Cellulitis (57.13%) was the most documented complication and no deaths were documented. Conclusion: According to this study most of the snake bite cases presented with signs of envenomation, of which larger  portion had neurotoxic manifestations. No deaths were documented due to early shifting to hospital and effective man agement of the cases.
Keywords: Snake bite; Signs of envenomation; Neurotoxic manifestations; Anti Snake Venom (ASV); Non-poisonous snakes